Development of reverse phase high performance liquid chromatographic method and method validation of paracetamol by using economical single mobile phase - Saha, S.; Dey, B. K.; Chakrabotry, S.; Choudhury, T. (Creative Pharma Assent, 2013)
The computerization of method development and validation are useful in analysis of pharmaceuticals in pharmaceutical industry. In this article a simple, sensitive, and precise high performance liquid chromatographic (HPLC) method for the analysis of Paracetamol with ultraviolet detection at 257 nm has been developed, validated, and used for the determination of compounds in commercial pharmaceutical products. Paracetamol tablet dosage form (two brands) was purchased from market and was from Glaxo Smith Kline (Calpol) and from IPCA (Pacimol) respectively. The compounds were well separated on a Hypersil ODS C18 reversed-phase column by use of a mobile phase consisting of methanol and water (90:10v/v at a flow rate of 1.0 ml.min). The linearity ranges were 20- 100µg/ ml for Paracetamol. Limits of detection (LOD) obtained 3.298g/ml limit of quantitation (LOQ) were 9.875g/ml Paracetamol. The study showed that reversed-phase liquid chromatography is sensitive and selective for the determination of Paracetamol using single mobile phase.